Using morphology-equivalent method to simulate the evolution of shrinkage in Ti6Al4V alloy castings during HIP. (May 2019) - Xu, Q; Zhou, J X; Li, W; Feng, X; Nan, H; Yin, Y J
Abstract: Hot isostatic pressing(HIP) is an effective method to eliminate the shrinkage in castings. The morphology of shrinkage is complex, and there are structures such as sharp corners and small passages which would lead to a large number of elements and easily divergent calculation results. Therefore, the application of numerical simulation in HIP is limited. To solve the non-convergence problem, the real shrinkage is often simplified as a sphere. However, this simplification ignores the characteristics of the shrinkage and makes the simulation results unreliable. In this paper, the technique of morphology-equivalent ellipsoid is applied to the numerical simulation of shrinkage evolution during HIP. Firstly, the 3D morphology of shrinkage in Ti6Al4V alloy castings is obtained by micro computed tomography. The radius of sphere and the geometric size and orientation of morphology-equivalent ellipsoid are calculated by corresponding equivalent techniques. Secondly, the numerical simulations of HIP for the Ti6Al4V castings before and after the equivalent method are carried out. The volume evolution of three kinds of shrinkages are recorded and compared. The results show that the volume evolution of the morphology-equivalent ellipsoid is closer to that of the real shrinkage, the feasibility of the morphology-equivalent ellipsoid and the limitations of sphere are verified.